Vectors of Exchange: Translation Praxis in Cuadernos de Marcha and Revista Casa de las Américas - Guzmán, María (TTR, 2015)
Historically, translation has been at the core of intellectual projects in Latin America and the Caribbean. This article investigates the translation praxis of two influential twentieth-century Latin American and Caribbean cultural journals whose influence reached beyond their own national borders: the Uruguayan Cuadernos de Marcha and the Cuban Revista Casa de las Américas. This paper examines the translation practices of these periodicals focusing on the material selected for translation. Looking at the discursive compositions that are constructed through translation, it discusses the vectors of intellectual exchange as they can be traced via translation, the way in which these periodicals create images of the Americas as a territory, and the extent to which these images either conform to or challenge the historical discursive practices that contribute to shaping existing regional imaginaries.